LITERASI AL-QUR’AN ANAK USIA DINI MELALUI METODE UMMI (Studi Kualitatif Deskriptif di TK Bunayya Islamic Pre School Kebayoran Lama Jakarta selatan) - Lathofah Marha; Fadlullah; Siti Khosiah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of early childhood Quranic literacy through the Ummi method, identify supporting and inhibiting factors in its implementation, and determine the results of its implementation at Bunayya Islamic Preschool Kindergarten in Kebayoran Lama, South Jakarta. The study used a descriptive qualitative approach with research subjects including the principal, the Ummi method coordinator, teachers, and students. Data were collected through observation, interviews, and documentation, then analyzed through the stages of data reduction, data presentation, and drawing conclusions. Data validity was carried out through triangulation, member checks, extended observations, and peer discussions. The results showed that the implementation of Quranic literacy through the Ummi method has been carried out in a structured, systematic manner, and in accordance with the Ummi Foundation quality standards. Learning is carried out through appropriate planning, grouping students based on their reading ability, the use of classical and individual strategies, and the use of interesting learning media. Supporting factors include the competence of certified teachers, regular supervision, adequate learning facilities, and school support. Inhibiting factors include limited classroom space, children's easily distracted concentration, and lack of repetition of reading at home. The results of the implementation show the child's ability to recognize hijaiyah letters, read with correct makhraj, use Ummi's typical rhythm, master basic Arabic numbers, and show a positive attitude and love for the Koran. In conclusion, Ummi's method is effective in increasing Al-Quran literacy in early childhood. Keywords: Al-Quran literacy, early childhood, Ummi method, Al-Quran learning.